Penerapan Metode Waterfall Pada Aplikasi Pembelajaran Seni Budaya Berbasis Website Menggunakan Framework Reactjs - Ibnu Choldun; Reni Rahmadewi (Peneliti.net, 2023)
The rapidly developing information technology has influenced various aspects of human life, especially in the field of arts and culture which is being forgotten by society. However, it has positive potential that we can utilize by using the internet as a promotional medium to introduce culture and arts to the wider community. Therefore, the development of a web-based cultural art learning application becomes an effective alternative in facilitating digital learning of cultural arts. In the development of this application, the waterfall method is used along with UML diagrams to visualize the software-based model in the form of use case diagrams, activity diagrams, and class diagrams. The application is designed using the JavaScript programming language with the ReactJs, Redux, ExpressJs, MySQL, and Sequelize frameworks using the Visual Studio Code code editor. The result of this research is a web-based cultural art learning application. Based on testing, the application runs and functions well, and it is responsive to mobile and desktop displays. Thus, this application is expected to be useful for the wider community as an alternative to facilitating digital learning of cultural arts.